Design and Validation of a Professional Development Model for Senior Managers at the University of Applied Science and Technology for Sustainable Development - Poorghasemi, Poorya; Parsa Moein, Koroush; Afkaneh, Soghra (Management Strategies and Engineering Sciences, 2025)
The present study aimed to design and validate a professional development model for senior managers at the University of Applied Science and Technology to promote sustainable development. The research employed a qualitative method, specifically meta-synthesis and the Delphi technique. The statistical population included scientific documents and organizational and academic experts. For the systematic literature review, a non-random purposive sampling method was used to select theoretical foundations and prior research (27-item checklist based on the PRISMA model). Similarly, non-random purposive sampling was employed for selecting experts. Data collection for the systematic review involved studying books, journals, online resources, and databases. After selecting the sources, data extraction and translation of relevant texts were conducted. Additionally, semi-structured interviews were used in the expert interview section. In the systematic review section, data collection tools were documentary studies aligned with the research approach of systematically reviewing the literature. Semi-structured interviews were also employed in this part of the study. To assess validity, the term "credibility" was applied. Furthermore, the validity of the questionnaire was established using face validity, content validity, and construct validity. Reliability was calculated and confirmed using Cronbach's alpha and composite reliability coefficients. Data analysis was performed using theoretical coding based on thematic analysis with MAXQDA software. The results indicated that the dimensions of professional development for senior managers at the University of Applied Science and Technology include cognitive development (self-awareness, knowledge acquisition, research competence, and understanding organizational learning processes), behavioral-judgmental development (value development, attitude development, and interest development), managerial-leadership development (organizational management skills, environmental adaptability, functional development, and guidance capabilities), and spiritual-ethical development (leadership ethics, ethical behavior development, and normative development).